Differentiation of lethal and non lethal prostate cancer: PSA and PSA isoforms and kinetics - Ballentine Carter, H (Nature Publishing Group, 2012)
Prostate-specific antigen (PSA) testing for the early diagnosis of prostate cancer has led to a decrease in cancer mortality. However, the high prevalence of low-grade prostate cancer and its long natural history, competing causes of death in older men and treatment patterns of prostate cancer, have led to dramatic overtreatment of the disease. Improved markers of prostate cancer lethality are needed to reduce the overtreatment of prostate cancer that leads to a reduced quality of life without extending life for a high proportion of men. The PSA level prior to treatment is routinely used in multivariable models to predict prostate cancer aggressiveness. PSA isoforms and PSA kinetics have been associated with more aggressive phenotypes, but are not routinely employed as part of prediction tools prior to treatment. PSA kinetics is a valuable marker of lethality post treatment and routinely used in determining the need for salvage therapy.